2013
DOI: 10.1155/2013/578479
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of Cytokines in Adipose Stem Cell-Conditioned Medium on the Migration and Proliferation of Skin FibroblastsIn Vitro

Abstract: Although adipose stem cell-conditioned medium (ASC-CM) has demonstrated the effect of promoting the cutaneous wound healing, the mechanism for this response on the effector cells (e.g., dermal fibroblasts) during the process remains to be determined. In this study, we aim to investigate the types and contents of cytokines in ASC-CM and the effects of some kinds of common cytokines in ASC-CM, such as EGF, PDGF-AA, VEGF, and bFGF, on dermal fibroblasts proliferation and migration in wound healing process. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 33 publications
1
46
0
1
Order By: Relevance
“…During the wound healing process, skin-resident cells are influenced by growth factors and other proteins secreted by MSCs, such as FGF 2 , EGF, KGF, and TGF-β (Zhao, Hu, Liu, Gong, & Chen, 2013;Zhou et al, 2013). In this sense, the conditioned medium of MSCs is a powerful source of these factors (Zhao et al, 2013). In the present study, the paracrine effect of DSCs and ASCs on cutaneous wound healing was evaluated by their action on human dermal fibroblasts and keratinocytes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…During the wound healing process, skin-resident cells are influenced by growth factors and other proteins secreted by MSCs, such as FGF 2 , EGF, KGF, and TGF-β (Zhao, Hu, Liu, Gong, & Chen, 2013;Zhou et al, 2013). In this sense, the conditioned medium of MSCs is a powerful source of these factors (Zhao et al, 2013). In the present study, the paracrine effect of DSCs and ASCs on cutaneous wound healing was evaluated by their action on human dermal fibroblasts and keratinocytes.…”
Section: Discussionmentioning
confidence: 92%
“…Divergences in the methodology between studies could explain the discrepancy in the findings. During the wound healing process, skin-resident cells are influenced by growth factors and other proteins secreted by MSCs, such as FGF 2 , EGF, KGF, and TGF-β (Zhao, Hu, Liu, Gong, & Chen, 2013;Zhou et al, 2013). In this sense, the conditioned medium of MSCs is a powerful source of these factors (Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the article titled “The Effects of Cytokines in Adipose Stem Cell-Conditioned Medium on the Migration and Proliferation of Skin Fibroblasts In Vitro ” [1], the pictures used in Figure 1(d) are the same as the pictures used in Figures 2(a1)–2(a4) of another article by the same authors, Li et al, “Side-by-Side Comparison of the Biological Characteristics of Human Umbilical Cord and Adipose Tissue-Derived Mesenchymal Stem Cells,” BioMed Research International, vol. 2013, Article ID 438243, 12 pages, 2013. doi: 10.1155/2013/438243.…”
mentioning
confidence: 99%
“…CM was then applied to HDFs at varying dilution folds (0%, 10%, 50% and 100%) in DMEM/F12 with 2% FBS. Using the same cellular model, Zhao et al [57] showed that CM collected from ASCs (at passage 3-7) cultured for an additional 48 h in serum-free DMEM/F12, at 50% dilution, promoted the proliferation and migration of HDFs. To analyze the effects of ASC-CM on ASCs, HDFs, normal primary human umbilical vein endothelial cells (HUVECs), and human keratinocytes, Kober et al [58] used CM collected from stem cell-enriched stromal vascular fraction (SVF) cultured in either FBS-free or FBS-supplemented DMEM for 20 h. ASC-CM was used at a 1:1 dilution on cell cultures.…”
Section: In Vitro Studiesmentioning
confidence: 99%